Islamophobia in higher education : combating discrimination and creating understanding - Ahmadi, Shafiqa; Cole, Darnell; Harper, Shaun R., 1975- (Stylus Publishing, 2020)
"While Islamophobia was present in our society before 9/11, it has become more pervasive in recent years. This is evidenced by the current social and political climate, hate speech and hate crimes directed at Muslims, and the Supreme Court's upholding of Presidential Proclamation 645 that effectively bans Muslim immigration from coming to the U.S. What does this mean for Muslim students in college, and indeed for institutions of higher education as they navigate law and policy on the one hand and adhere to their mission of achieving inclusive and equitable educational environments on the other?"--